Repair of an Extensive Furcation Perforation with CEM Cement: A Case Study - Eghbal, Mohammad Jafar; Fazlyab, Mahta; Asgary, Saeed (Iranian Endodontic Journal, 2013)
Iatrogenic perforation of the furcation area in multi-rooted molars during preparation of the access cavity can potentially lead to tooth extraction. The present case report describes the nonsurgical endodontic management of an extensive pulp chamber floor perforation in a first mandibular molar with calcium enriched mixture (CEM) cement. The perforation was chemically cleaned and then physically sealed with CEM cement. Root canal therapy was completed and the tooth was then restored with amalgam. A one-year follow-up revealed the absence of symptoms of infection/inflammation as well as clinical and radiographic signs/symptoms and therefore, can be interpreted as a favorable treatment outcome.